2015
DOI: 10.1002/btpr.2045
|View full text |Cite
|
Sign up to set email alerts
|

Purification, immobilization, and biochemical characterization ofl‐arginine deiminase from thermophilicAspergillus fumigatusKJ434941: Anticancer activityin vitro

Abstract: l-Arginine deiminase (ADI) has a powerful anticancer activity against various tumors, via arginine depletion, arresting the cell cycle at G1 phase. However, the current clinically tried bacterial ADI displayed a higher antigenicity and lower thermal stability. Thus, our objective was to purify and characterize this enzyme from thermophilic fungi, to explore its catalytic and antigenic properties for therapeutic uses. ADI was purified from thermophilic Aspergillus fumigatus KJ434941 to its electrophoretic homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 67 publications
3
61
1
Order By: Relevance
“…15,16 In the study by El-Sayed et al on ADI isolated from thermophilic Aspergillus fumigatus KJ434941, there was an overall three-fold increase in the plasma half-life of the enzyme upon pegylation. 17 The kinetic data of Km and Vmax values of PEGylated ADI was found to be 2.94 ± 0.13 mM and 129.87 ± 1.24 µmol/min, respectively. The Km value of the ADI was found to be slightly increased upon pegylation, which suggested that the attached PEG molecules on the surface of the enzyme did not significantly reduce the affinity for the substrate.…”
Section: Resultsmentioning
confidence: 88%
“…15,16 In the study by El-Sayed et al on ADI isolated from thermophilic Aspergillus fumigatus KJ434941, there was an overall three-fold increase in the plasma half-life of the enzyme upon pegylation. 17 The kinetic data of Km and Vmax values of PEGylated ADI was found to be 2.94 ± 0.13 mM and 129.87 ± 1.24 µmol/min, respectively. The Km value of the ADI was found to be slightly increased upon pegylation, which suggested that the attached PEG molecules on the surface of the enzyme did not significantly reduce the affinity for the substrate.…”
Section: Resultsmentioning
confidence: 88%
“…Among them ADI is one of the most important and best characterized enzymic drugs. The earlier application of ADI is focused against the treatment of hepatocellular carcinomas but in the recent past, scientific community trying to search new therapeutic applications of ADI in treatment of other arginine auxotrophic tumors such as pancreatic cancer (Liu et al, 2014), prostate cancer (Changou et al, 2014), leukemia (Miraki-Moud et al, 2015), colon cancer (El-Sayed et al, 2015), and breast cancer (Li et al, 2016). As we know that, ADI is a significant player of ADI or arginine dihydrolase (ADH) pathway and generating one molecule of ATP by phosphorylation of ADP.…”
Section: Effect Of Mineral Ions and Amino Acidsmentioning
confidence: 99%
“…The crude peroxidase was fractionated by ammonium sulfate saturation (20-70%), incubation at 4°C for 2 h, then the mixture was centrifuged for 10 min at 4000 g. The precipitated protein was collected in potassium phosphate buffer containing 1 mM EDTA and dialyzed against the same buffer till complete removal of salt traces. The enzyme was purified by gel filtration chromatography using Sephadex G 100 and G 200 columns [26,[30][31][32]. After column equilibration with the same buffer, the sample was loaded to the column and the enzyme fractions were eluted at flow rate 0.2 ml/ min.…”
Section: Purification Molecular Subunit Structure and Zymogram Analymentioning
confidence: 99%
“…The mixture was centrifuged for 10 min at 5000 rpm, the activated chitosan was washed with distilled water, collected and suspended in 10 ml potassium phosphate buffer (pH 7.0). The glutaraldehyde-activated chitosan has free reactive aldehyde groups that form Schiff base with the reactive amino groups of peroxidase [32]. One ml of peroxidase (35.0 µmol/mg) was added to the 5 ml activated chitosan, incubated overnight at 4°Cwith gently shaking.…”
Section: Covalent and Entrapment Immobilization Of The Purified A Flmentioning
confidence: 99%